2020
DOI: 10.1002/ana.25900
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Variability in Spinal Muscular Atrophy Type III

Abstract: Objective: We report natural history data in a large cohort of 199 patients with spinal muscular atrophy (SMA) type III assessed using the Hammersmith Functional Motor Scale Expanded (HFMSE). The aim of the study was to establish the annual rate and possible patterns of progression according to a number of variables, such as age of onset, age at assessment, SMN2 copy number, and functional status. Methods: HFMSE longitudinal changes were assessed using piecewise linear mixed-effects models. The dependency in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 33 publications
7
47
3
Order By: Relevance
“…Studies with a larger sample size and further analyses are needed to confirm whether this demonstrates a peak in grip strength as shown in previous findings, where upper limb strength (expressed in absolute values) increased before the age of 14 and decreased after 21 . Similarly, a recent, retrospective study in patients with Type 3 SMA demonstrated increased motor function, as measured by the HFMSE, up to the age of 7 and a decrease beyond this age 35 . A similar time course in motor function has been observed in DMD, where the distance covered in a 6MWT continuously increased before the age of 7 and decreased thereafter 37 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Studies with a larger sample size and further analyses are needed to confirm whether this demonstrates a peak in grip strength as shown in previous findings, where upper limb strength (expressed in absolute values) increased before the age of 14 and decreased after 21 . Similarly, a recent, retrospective study in patients with Type 3 SMA demonstrated increased motor function, as measured by the HFMSE, up to the age of 7 and a decrease beyond this age 35 . A similar time course in motor function has been observed in DMD, where the distance covered in a 6MWT continuously increased before the age of 7 and decreased thereafter 37 .…”
Section: Discussionsupporting
confidence: 59%
“…Current clinical measures have a low sensitivity to change over 12 months: the SRM of the RULM over 12 months is 0.14 33 and the mean change in the 6MWT over 12 months is low (−7.8 m/year) and age dependent 34 . A recent study has also illustrated that the SRM of HFMSE in patients with Type 3 SMA is low and very variable according to age and ambulant status 35 . In this study, we aim to identify additional ways to detect a change in SMA severity over shorter periods.…”
Section: Discussionmentioning
confidence: 99%
“…While the early real‐world data have mainly focused on type I patients, 8 , 9 , 10 , 11 and more recent studies have reported data in adults, 12 , 13 , 14 , 15 , 16 , 17 , 18 less has been reported in pediatric patients or, more generally, to cover the spectrum of treated younger and older type III patients who were also not included in the pivotal trials. 19 Furthermore, as there is reported evidence of the variability of the progression of type III in relation to a number of variables, such as age and functional status, 20 , 21 , 22 the interpretation of the limited real‐world data available is also affected by the lack of comparison with reference data from untreated patients.…”
Section: Introductionmentioning
confidence: 99%
“…While any improvement in a neurodegenerative disease could be regarded as a treatment effect, previous natural history studies have shown that individual improvements in some motor scales in a timeframe less of that two years are not infrequent in the adult population. 18, [28][29][30][31] Moreover, in the last years, treatments such as salbutamol or pyridostigmine are frequently used off-label for the treatment of SMA patients and could have a positive effect in motor scales, 32 erroneously attributed to nusinersen. Accordingly, a recent systematic review highlighted that the scarcity of data, the phenotypic variability, slow disease progression and the limited sensitivity of available outcome measures difficult to draw definitive conclusions about the natural history of the disease in short timeframes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our and previous natural history studies show that a non-negligible proportion of "untreated" adult patients experience improvements that could be considered clinically meaningful, when followed for less than two years. 18, [28][29][30][31] These unexpected improvements could be due to three facts: test-retest inaccuracies in the scales; functional fluctuations, which are frequently reported by patients (e.g. depending on the season of the year); or to the fact that some "untreated" patients have actually started other treatments (e.g.…”
Section: Discussionmentioning
confidence: 99%